A Gel Formulation Containing a New Recombinant Form of Manganese Superoxide Dismutase: A Clinical Experience Based on Compassionate Use-Safety of a Case Report - Lucia Grumetto; Antonio Del Prete; Giovanni Ortosecco; Antonella Borrelli; Salvatore Del Prete; Aldo Mancini (Case Reports in Ophthalmological Medicine)
Background. We report a case of bilateral posterior subcapsular cataracts (PSCs) in a 24-year-old man with an allergic conjunctivitis history caused by a long-term therapy with glucocorticoids. Case Presentation. The patient showed a visual acuity of 9/10 for both eyes. He followed a therapy with ketotifen and bilastine for four years. During the last six months before our evaluation, he was treated with chloramphenicol and betamethasone, interrupted for onset of cataracts and increased intraocular pressure. We treated him with ophthalmic gel preparation containing a new recombinant form of manganese superoxide dismutase (rMnSOD) at a concentration of 12.5 μg/mL, only for the right eye, while left eye was treated with standard protocol of Bendazac-lysine g 0.5. Conclusion. This case report shows the protective effects of rMnSOD versus PSC disease, probably due to the capacity of rMnSOD of countering free radical species.